Different views on Digital Scholarship: separate worlds or cohesive research field? - Juliana E. Raffaghelli; Stefania Cucchiara; Flavio Manganello; Donatella Persico (Association for Learning Technology, 2016)
This article presents a systematic review of the literature on Digital Scholarship, aimed at better understanding the collocation of this research area at the crossroad of several disciplines and strands of research. The authors analysed 45 articlesin order to draw a picture of research in this area. In the first phase, the articles were classified, and relevant quantitative and qualitative data were analysed. Results showed that three clear strands of research do exist: Digital Libraries, Networked Scholarship and Digital Humanities. Moreover, researchers involved in this research area tackle the problems related to technological uptake in the scholar's profession from different points of view, and define the field in different - often complementary - ways, thus generating the perception of a research area still in need of a unifying vision. In the second phase, authors searched for evidence of the disciplinary contributions and interdisciplinary cohesion of research carried out in this area through the use of bibliometric maps. Results suggest that the area of Digital Scholarship, still in its infancy, is advancing in a rather fragmented way, shaping itself around the above-mentioned strands, each with its own research agenda. However, results from the cross-citation analysis suggest that the Networked Scholarship strand is more cohesive than the others in terms of cross-citations.